Analysis of the Impact of the Video Maker-Based PjBL Model on Motivation and Mathematics Learning Outcomes of Middle School Students: An Experimental Study - fajar iyah Hani’atul (Journal of Education Technology and Inovation, 2024)
The purpose of this study was to determine the impact of the Video Maker-Based PjBL Model on the Motivation and Learning Outcomes of Junior High School Mathematics Students. The role of Mathematics teachers in using the PjBL (Project Based Learning) Model based on the use of Video Maker shows the importance of real context according to the situation in the environment by students themselves in thinking deeply to identify problems in learning so that the concepts received by students are more meaningful. This research is in the form of a quantitative experiment with the research subjects of VIII grade students at SMPN 1 Gumukmas-Jember, school year 2023/2024. The main objective in this study is to improve students' Learning Motivation and Mathematics learning outcomes (cognitive) of students. The data in this study are quantitative data obtained from tests of students' knowledge and understanding through questionnaire tests. The results of the t test and F test of the success of this study show: (1) the effect of the PjBL (Project Based Learning) Model Based on the Use of Video Maker on increasing student Learning Motivation is 5.469, (2) the effect of the PjBL (Project Based Learning) Model Based on the Use of Video Maker on increasing student learning outcomes is 8.007, and (3) the effect of the PjBL (Project Based Learning) Model Based on the Use of Video Maker on increasing student Learning Motivation and student Learning Outcomes together is 9.471. This means that the application of the PjBL (Project Based Learning) Model Based on the Use of Video Maker in increasing students' Learning Motivation and Learning Outcomes has a significant effect